Susceptibility profile of clinical and food-associated Listeria monocytogenes strains to a commercial phage product using different test methods - Brieske, Christoph; Böhnlein, Christina; Low, Hui Zhi; Franz, Charles M. A. P. (Frontiers in Microbiology, 2025)
Foodborne bacterial pathogens continue to pose a significant global health and economic burden, with Listeria monocytogenes being a persistent risk due to its frequent involvement in outbreaks and food recalls. Bacteriophage-based products are promising tools for enhancing food safety, yet systematic evaluations across genetically diverse L. monocytogenes strains are limited. In this study, we assessed the efficacy of a commercially available Listeria-specific phage product against 50 whole-genome-sequenced clinical and food-associated L. monocytogenes isolates recently collected in Germany. Traditional spot and plaque assays indicated 70–76% susceptibility, whereas viability-based methods, including colony reduction, OD600 measurement, and flow cytometry, demonstrated substantial bacterial reduction across all isolates within 24 h. Notably, flow cytometry revealed a marked decline in viable cells as early as 3 h post-treatment. By systematically comparing susceptibility assays, we argue that modern viability-based methods assessing microbial load reduction offer key advantages over classical plaque assays for evaluating phage efficacy in food safety applications. While plaque assays remain valuable primarily for determining infectivity, reduction-based approaches have the potential to serve as a measure of antimicrobial performance in biocontrol settings.